Management of Third World Crises in Adverse Partnership : Theory and Practice - Bokhari, Imtiaz H. (GHQ, Rawalpindi Army Education Publishing House, 2002)
Imtiaz Bokhari details the world response to three regional conflicts--the 1973 Arab-Israeli war, the 1971 Indo-Pak crisis, and the Iran-Iraq war--and analyzes the dynamics of the comcomitant international crisis management. There exists a greater need for crisis management, the author argues, in a international system in which the disintegration of the old superpower competition and restraints has changed the rules of the game to the apparent advantage of the stronger regional powers.
Include Bibliography and Index.
This three-part volume details the world response to three regional conflicts - the 1973 Arab-Israeli War, the 1971 Indo-Pakistan crisis and the bitterly-fought Iran-Iraq border war - and examines the concepts and dynamics of crisis management in relation to these conflicts.
Keywords: International relations -- India-Pakistan Conflict (1971) -- Crisis management -- Iran-Iraq War (1980-1988) -- Israel-Arab War (1973) -- Peace